ANALYSIS OF FARMER’S SATISFACTION ON INTI COMPANY SERVICE OF BROILER PARTNERSHIPS IN BALI - I. W., SUKANATA; WIJANA, I. W. (Majalah Ilmiah Peternakan, 2024)
The Inti-Plasma partnership system in broiler chicken farms in Bali developed rapidly after the monetary crisis 1997. Large companies as the Inti have a stronger bargaining position than the farmers (plasma) as their partners. So that the Inti company has a more dominant role in determining the contents of the partnership agreements. This study aims to see how of the farmer’s satisfaction to the service quality of the Inti company. The service quality is seen based on several service dimension such as; physical evidence, reliability, responsiveness, assurance, and em- pathy. The data used is primary data collected through interviews with 100 farmers who took part in partnerships who were randomly selected from 8 districts in Bali. Data were analyzed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The level of farmer satisfaction to the service quality of the Inti company reached 76.05%. This shows that the quality of the Inti company’s service to the farmers is re- ally need to be improved, especially in relation to the physical dimension (CSI Tangible 72.16%) and the guarantee dimension (CSI Assurance 73.87%). Attributes of service quality that should be a top priority for improvement are; Day Old Chick (DOC) quality, harvest age, partnership agreement, Harvest-payment time interval to the farmers, performance standards, farmer income, DOC guarantee, and the price of production facilities.